1998
DOI: 10.1002/(sici)1097-4636(19980315)39:4<539::aid-jbm6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Improved local delivery of TGF-?2 by binding to injectable fibrillar collagen via difunctional polyethylene glycol

Abstract: To overcome rapid diffusion and clearance from the implant site and to increase stability, recombinant transforming growth factor beta2 (TGF-beta2) was covalently bound to injectable bovine dermal fibrillar collagen (FC) and its activity compared to admixed TGF-beta2. Covalent binding was achieved in a two-step procedure: First, TGF-beta2 was reacted with the difunctional polyethylene glycol (PEG) linker, and then the PEG-attached TGF-beta2 (PEG-TGF-beta2) was bound to the fibrillar collagen (FC-PEG-TGF-beta2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Finally, the actual amounts of Tgf-␤3 released from the collagen gel were not quantified in the perisutural tissues, and the sutures in the Tgf-␤3 groups may have received smaller amounts than anticipated. However, studies using this collagen gel vehicle have shown that Tgf-␤2 mixed with the collagen gel in culture retained a level of activity similar to that of Tgf-␤2 alone (Schroeder-Tefft et al, 1997;Bentz et al, 1998). The collagen lasted for at least 63 days in rabbit perisutural tissue, as observed by the use of biotinylated collagen gel (Moursi et al, unpublished data), and it showed no evidence of a localized inflammatory or generalized immune response following gel implantation (Chong et al, 2001(Chong et al, , 2002Mooney et al, 2002a;Opperman et al, 2002b) (Moursi et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the actual amounts of Tgf-␤3 released from the collagen gel were not quantified in the perisutural tissues, and the sutures in the Tgf-␤3 groups may have received smaller amounts than anticipated. However, studies using this collagen gel vehicle have shown that Tgf-␤2 mixed with the collagen gel in culture retained a level of activity similar to that of Tgf-␤2 alone (Schroeder-Tefft et al, 1997;Bentz et al, 1998). The collagen lasted for at least 63 days in rabbit perisutural tissue, as observed by the use of biotinylated collagen gel (Moursi et al, unpublished data), and it showed no evidence of a localized inflammatory or generalized immune response following gel implantation (Chong et al, 2001(Chong et al, , 2002Mooney et al, 2002a;Opperman et al, 2002b) (Moursi et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…[212] Also, recombinant TGF-b2, when covalently bound to fibrillar collagen (FC) via a difunctional PEG linker, was found to be more prolonged and stabilized in its effects both in vivo and in vitro. [213] Using a gradient maker based on photopolymerization of a gradient flow, the spatial distribution of growth factors can be controlled. [214] The potential importance of this control has been demonstrated by the finding that attachment of randomly distributed TGF-b on PEG gels increased matrix production by smooth muscle cells [215] while attachment of bFGF in a gradient fashion directed cell alignment and migration.…”
Section: Immobilizing Growth Factors To the Matrixmentioning
confidence: 99%
“…In an illustrative study, covalent bonding of VEGF and angiopoietin to porous collagen scaffolds was accomplished using 1-ethyl-3-(3-dimethylamino propyl) carbodiimide hydrochloride (EDC) chemistry [51,52]. Alternatively, VEGF and Transforming Growth Factor β2 (TGFβ2) have been conjugated to collagen scaffolds using various bifunctional cross-linkers [53,54]. As another promising approach that models native GF-ECM interactions, collagen scaffolds have been covalently decorated with heparin, followed by the noncovalent attachment of GFs that naturally harbor heparin-binding domains [5557].…”
Section: Functionalizing Bone-mimetic Scaffolds With Growth Factorsmentioning
confidence: 99%